غالبؔ کی غزلیہ زمینوں میں پاکستانی شعرا کی نعت گوئی کا ایک جائزہ - Sahar, Naseem (Zoraiz, 2022)
An important aspect of the recognition of Ghalib's poetic greatness is that many poets have written poetry by following his patterns of rhythm and rhymes. Natia's poetry is also included in this poetry. This thesis consists of the evaluation of such type of Natia poetry by Pakistani poets. In it, as a sample, selected verses of Naats of various poets on the patterns of rhythm and rhymes of the first ghazal of Dewan-e-Galib are given and it is evaluated what additions these poets have made regarding topic and art in their naats.